Short- and Long-Term Results of Xenogeneic-Free Cultivated Autologous and Allogeneic Limbal Epithelial Stem Cell Transplantations. Issue 12 (December 2019) - Behaegel, Joséphine; Zakaria, Nadia; Tassignon, Marie-José; Leysen, Inge; Bock, Felix; Koppen, Carina; Ní Dhubhghaill, Sorcha
Abstract : Purpose: To evaluate the short- and long-term success rates of xenogeneic-free cultivated limbal epithelial stem cell transplantation (CLET) for the treatment of limbal stem cell deficiency (LSCD). Methods: Thirteen patients with LSCD underwent an autologous (n = 9) or allogeneic (n = 4) CLET. The primary end point was to assess the long-term anatomical success rate of transplanted grafts at a follow-up of at least 3 years, in comparison with the short-term outcomes. Secondary end points involved reviewing functional improvement, patient-reported symptoms, and change in percentage area of corneal vascularization in both short-term and long-term. Results: The mean short- and long-term follow-up periods were 2.1 ± 0.38 years and 6.7 ± 1.81 years, respectively. The total anatomical success rate was 46.1% in the short-term, but it decreased to 23.1% in the long-term. A partial success rate of 30.8% was observed in both short- and long-term, and the failure rate increased from 23.1% to 46.1%. The mean percentage of vessel area decreased from 12.11% ± 5.29% preoperatively to 7.82% ± 6.70% in the short-term and increased to 8.70% ± 6.32% in the long-term. There was a significant improvement in best-corrected visual acuity ( P = 0.044) in the short-term although not in the long-term ( P = 0.865). Conclusions: This study shows that anatomical and functional success rates of CLET decrease over time. We believe that the decline of success is related to the extent of disease, cell origin, and lack of niche protection because subtotal LSCD and autologous donor cells confer a higher chance of success in the long-term.